Local Coffee-Based Product Innovation as a New Attraction for Gastronomic Tourism - WINARTI, Ni Kadek; YENI, Ni Putu Helda Anggara; ANANDA, Kadek Tia Dwi; PRAMESWARI, Anak Agung Sagung Mirah (Journal Management and Hospitality, 2025)
Gastronomic tourism has rapidly emerged as a global trend, emphasizing lokal culinary experiences as key attractions. Catur Village in Kintamani, Bali, is known for producing high-quality arabica coffee and holds great potential for development as a gastronomic tourism destination. This study aims to explore local product innovation based on coffee, particularly the development of coffee peel jam, as a new attraction for community-based and sustainable tourism. The research applied a qualitative approach using observation, interviews, and documentation techniques. The findings reveal that the innovation of coffee peel jam not only provides economic added value but also strengthens social and environmental aspects through circular economy practices. Active involvement of the local community, such as the Catur Paramitha production group, is a key factor in the success of this product innovation. Furthermore, the product serves as an educational tool and cultural preservation medium that enhances the competitiveness of the tourism destination. Thus, coffee-based local products significantly contribute to the advancement of sustainable tourism at the village level.